Hydrochemical Characteristics, Controlling Factors, and High Nitrate Hazards of Shallow Groundwater in an Urban Area of Southwestern China - Chang Yang; Si Chen; Jianhui Dong; Yunhui Zhang; Yangshuang Wang; Wulue Kang; Xingjun Zhang; Yuanyi Liang; Dunkai Fu; Yuting Yan; Shiming Yang (Toxics, 2025)
Groundwater nitrate (NO3−) contamination has emerged as a critical global environmental issue, posing serious human health risks. This study systematically investigated the hydrochemical processes, sources of NO3− pollution, the impact of land use on NO3− pollution, and drinking water safety in an urban area of southwestern China. Thirty-one groundwater samples were collected and analyzed for major hydrochemical parameters and dual isotopic composition of NO3− (δ15N-NO3− and δ18O-NO3−). The groundwater samples were characterized by neutral to slightly alkaline nature, and were dominated by the Ca-HCO3 type. Hydrochemical analysis revealed that water–rock interactions, including carbonate dissolution, silicate weathering, and cation exchange, were the primary natural processes controlling hydrochemistry. Additionally, anthropogenic influences have significantly altered NO3− concentration. A total of 19.35% of the samples exceeded the Chinese guideline limit of 20 mg/L for NO3−. Isotopic evidence suggested that primary sources of NO3− in groundwater include NH4+-based fertilizer, soil organic nitrogen, sewage, and manure. Spatial distribution maps indicated that the spatial distribution of NO3− concentration correlated strongly with land use types. Elevated NO3− levels were observed in areas dominated by agriculture and artificial surfaces, while lower concentrations were associated with grass-covered ridge areas. The unabsorbed NH4+ from nitrogen fertilizer entered groundwater along with precipitation and irrigation water infiltration. The direct discharge of domestic sewage and improper disposal of livestock manure contributed substantially to NO3− pollution. The nitrogen fixation capacity of the grassland ecosystem led to a relatively low NO3− concentration in the ridge region. Despite elevated NO3− and F− concentrations, the entropy weighted water quality index (EWQI) indicated that all groundwater samples were suitable for drinking. This study provides valuable insights into NO3− source identification and hydrochemical processes across varying land-use types.